A brief overview on the dissolution mechanisms of sulfide minerals in acidic sulfate environments at low temperatures: Emphasis on electrochemical cyclic voltammetry analysis. (1st November 2020) - Zhang, Yisheng; Zhao, Hongbo; Qian, Lu; Sun, Menglin; Lv, Xin; Zhang, Luyuan; Petersen, Jochen; Qiu, Guanzhou
Highlights: The dissolution mechanisms of several sulfide minerals are summarized. The electrochemical CV studies of various minerals are shown. The inhibition factors (solid phase and semiconductor properties) are discussed. Several promising directions for further research are suggested. Abstract: (Bio)Hydrometallurgy is a relatively economical and eco-friendly processing technology for sulfide minerals. Sulfide minerals degradation at abandoned mine sites also results in complex environmental problems. Although extensive studies have been done to explore the dissolution mechanisms of various sulfide minerals in acidic (microbial) sulfate environments, a systematic comparison of the findings is still needed. This paper summarizes the research into the dissolution mechanisms of several sulfide minerals, predominantly under bioleaching conditions. Especially, electrochemical cyclic voltammetry studies of various minerals are shown. Additionally, effects on the solid phase, including decomposition products and precipitates formed during the degradation processes, are discussed.